Efektivitas model pembelajaran role playing terhadap hasil belajar kognitif aritmatika sosial pada materi uang dan perdagangan kelas v sekolah dasar - Fath Sadidan Burhanudin; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2025)
Social Arithmetic combines arithmetic with social contexts, emphasizing understanding and applying arithmetic principles in daily life and social situations. This study examines the effectiveness of the Role Playing learning model on cognitive learning outcomes in Social Arithmetic, focusing on money and trade topics among grade V students in Gugus Menur, Miri, Sragen. The research employs an experimental method with a quantitative approach, utilizing a control group pretest-posttest design. The population consists of all grade V students in Gugus Menur, with samples from two experimental and two control schools. Data analysis includes hypothesis testing using independent sample t-tests and n-gain tests. The findings show significant differences in cognitive understanding between the Role Playing and Think Pair Share (TPS) learning models after treatment. The Role Playing model is more effective than conventional learning, with a standard gain score of 0.50 (moderate) for the experimental class and 0.19 (low) for the control class. In conclusion, the Role Playing model significantly improves cognitive learning outcomes in Social Arithmetic compared to the TPS model among grade V students.